An Anticancer Rhenium Tricarbonyl Targets Fe−S Cluster Biogenesis in Ovarian Cancer Cells. Issue 43 (27th September 2022) - Neuditschko, Benjamin; King, A. Paden; Huang, Zhouyang; Janker, Lukas; Bileck, Andrea; Borutzki, Yasmin; Marker, Sierra C.; Gerner, Christopher; Wilson, Justin J.; Meier‐Menches, Samuel M.
Abstract: Target identification remains a critical challenge in inorganic drug discovery to deconvolute potential polypharmacology. Herein, we describe an improved approach to prioritize candidate protein targets based on a combination of dose‐dependent chemoproteomics and treatment effects in living cancer cells for the rhenium tricarbonyl compound TRIP. Chemoproteomics revealed 89 distinct dose‐dependent targets with concentrations of competitive saturation between 0.1 and 32 μM despite the broad proteotoxic effects of TRIP. Target‐response networks revealed two highly probable targets of which the Fe−S cluster biogenesis factor NUBP2 was competitively saturated by free TRIP at nanomolar concentrations. Importantly, TRIP treatment led to a down‐regulation of Fe−S cluster containing proteins and upregulated ferritin. Fe−S cluster depletion was further verified by assessing mitochondrial bioenergetics. Consequently, TRIP emerges as a first‐in‐class modulator of the scaffold protein NUBP2, which disturbs Fe−S cluster biogenesis at sub‐cytotoxic concentrations in ovarian cancer cells. Abstract : A dose‐dependent chemoproteomic approach to inorganic drug discovery improves the prioritization of candidate drug targets and revealed the scaffold protein NUBP2 involved in Fe−S cluster biogenesis as a relevant target for the rhenium tricarbonyl TRIP. This approach efficiently deconvolutes the polypharmacology of metal‐based drug candidates and may be generally applied.